2014
DOI: 10.4103/0971-5851.138993
|View full text |Cite
|
Sign up to set email alerts
|

Cytological study of palpable breast lumps presenting in an Indian rural setup

Abstract: Introduction:Benign as well as malignant breast lesions are quite common in Indian population. It is the second most common cancer site after cancer cervix. Fine-needle aspiration cytology (FNAC) is safe, reliable, and time saving outdoor procedure with little discomfort to the patient. FNAC is useful in diagnosis and further planning of treatment without need for biopsy. The current study was carried out with aims of studying the frequency of various breast lesions on FNAC in a rural area in India and its his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
8
18
2
Order By: Relevance
“…Breast lump as a clinical presentation was found more common in female (n=751; 97.41%) and male accounted for 20 cases (2.59%) only similar to the study done by Ahmed Omer Almobarak AO et al (Female: 94.86% and male: 5.24%). 9 Most of the breast lumps were neoplastic in origin (n=747; 84.14%) which was similar to the study conducted by Sankaye, SB et al 8 Benign cases was more common than malignant ones which was congruent to the study done by Ahmed Omer Almobarak AO et al and Shah SA et al 7,9 Fibroadenoma and fibrocystic changes were the most common benign lesion observed in this study similar to that found by Ahmed Omer Almobarak AO et al 9 Malignant cases accounted for 36 cases (4.7%) only, which was in contrast to the study done by Ahmed Omer Almobarak AO et al (248/759 cases; 32.67%). 9 Ductal carcinoma was the most common type of malignant breast lesion (30/ 36 cases; 83.33%) which was also found by Pudasaini S et al 10 The peak age group for the breast lumps was 20-40 years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Breast lump as a clinical presentation was found more common in female (n=751; 97.41%) and male accounted for 20 cases (2.59%) only similar to the study done by Ahmed Omer Almobarak AO et al (Female: 94.86% and male: 5.24%). 9 Most of the breast lumps were neoplastic in origin (n=747; 84.14%) which was similar to the study conducted by Sankaye, SB et al 8 Benign cases was more common than malignant ones which was congruent to the study done by Ahmed Omer Almobarak AO et al and Shah SA et al 7,9 Fibroadenoma and fibrocystic changes were the most common benign lesion observed in this study similar to that found by Ahmed Omer Almobarak AO et al 9 Malignant cases accounted for 36 cases (4.7%) only, which was in contrast to the study done by Ahmed Omer Almobarak AO et al (248/759 cases; 32.67%). 9 Ductal carcinoma was the most common type of malignant breast lesion (30/ 36 cases; 83.33%) which was also found by Pudasaini S et al 10 The peak age group for the breast lumps was 20-40 years.…”
Section: Discussionsupporting
confidence: 85%
“…Cytological study has further many advantages including easiness, cost effectiveness and accuracy. [6][7][8] Furthermore, cytological study has been well tolerated among individual as it gives early detection and treatment option. Breast lump as a clinical presentation was found more common in female (n=751; 97.41%) and male accounted for 20 cases (2.59%) only similar to the study done by Ahmed Omer Almobarak AO et al (Female: 94.86% and male: 5.24%).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also present in other studies. [10][11][12][13][14] In males the most common diagnosis was fibroadenoma with one case of ductal carcinoma (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Fine-needle aspiration cytology is a rapid and effective method for the primary categorization of palpable breast lumps into benign, malignant, atypical, suspicious, and unsatisfactory categories 6 . The most significant advantage of FNAC is the high degree of accuracy, rapid results, and a less invasive procedure than a tissue biopsy 7 .…”
Section: Discussionmentioning
confidence: 99%